RELATIONSHIP BETWEEN PROTON-PUMP INHIBITOR USE AND LOWER BLOOD MAGNESIUM LEVELS - Putri, Wenny Dwi; Andrajati, Retnosari; Supardi, Sudibyo (International Journal of Applied Pharmaceutics, 2018)
Objective: The aim of this study was to determine whether and to what degree proton-pump inhibitor (PPI) use affects blood magnesium levels. Methods: We performed a cross-sectional comparative study with consecutive sampling technique from June to October 2016. This study compared blood magnesium levels of patients using PPIs (lansoprazole and omeprazole) with those of patients not taking PPIs. The total sample was 184 patients. Data collected included questionnaires and medical records. Statistical analysis was performed with the unpaired t-test, Mann–Whitney U-test, and one-way analysis of variance. Results: The average magnesium level in patients using PPIs was 2.08±0.21 mg/dL, whereas the average magnesium level in patients not using PPIs was 2.27±0.38 mg/dL, a statistically significant difference (p<0.001). Magnesium levels were significantly lower in patients using PPIs for >1 year and in patients using omeprazole (p<0.05). Conclusion: Blood magnesium levels of patients using PPIs were significantly lower than those who did not use PPIs. Decreased levels of magnesium in patients using PPI are affected by PPI type and the duration of PPI use - >1 year. Thus, the long-term use of PPIs may lead to decreased levels of magnesium. Therefore, monitoring the levels of magnesium is important in patients using PPIs for a long term to avoid the risk of hypomagnesemia.